IPEDs Use in Recreational Sport Settings: Public Health Implications and Prevention Strategies - L. Lazuras (Emerging Trends in Drugs, Addictions, and Health)
Recreational sport and physical activity engagement are meant to promote healthy lifestyles across the lifespan and help individuals develop positive psychological skills and characteristics. The use of Image and Performance Enhancement Drugs (IPEDs) is against this idea and poses a significant health risk to users. IPEDs use is increasingly recognized as an emerging public health and societal challenge because it can directly affect millions of people engaging in recreational sport across countries. The present talk will provide an overview of the prevalence of IPEDs use in recreational sport settings and will discuss the latest evidence about the mental and physical health problems associated with this behaviour. The key social and psychological drivers of IPEDs use will be presented, with an emphasis on availability, accessibility, and patterns of use. Lastly, the existing legislative and policy measures to tackle IPEDs use in recreational sport will be reviewed. Drawing on international research projects and policy initiatives, the talk will discuss novel evidence-informed preventive strategies focusing on building positive psychological characteristics (e.g., mindfulness, acceptance, and self-compassion), and on developing a systems-based approach that involve multiple stakeholders, including National Anti-Doping Organisations, public health authorities, and the fitness industry.